1998
DOI: 10.1557/jmr.1998.0302
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy and x-ray structural investigation of La0.7Ca0.3MnO3 thin films

Abstract: The structural changes and magnetoresistance (MR) properties of as-grown and post-annealed La0.7Ca0.3MnO3 films were investigated by transmission electron microscopy (TEM) and x-ray diffraction (XRD). The data for the films were compared to that for bulk La0.7Ca0.3MnO3 post-annealed under the same conditions. The main structure of the as-grown films was face-centered pseudo-cubic with a doubled perovskite unit cell, of size ∼2ap × ∼2ap × 2ap, where ap is the single perovskite parameter. The phase showed a cube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
2
17
1
Order By: Relevance
“…Reconstruction of these five ED patterns suggests a body-centred cubic lattice structure in reciprocal space, corresponding approximately to a face-centred pseudo-cubic lattice in real space with a unit cell of 2a p  2a p  2a p . It is noteworthy that this pseudo fcc structure has also been reported in as-grown LCMO films on LaAlO 3 substrates [19].…”
Section: Electron Diffraction Patternssupporting
confidence: 71%
“…Reconstruction of these five ED patterns suggests a body-centred cubic lattice structure in reciprocal space, corresponding approximately to a face-centred pseudo-cubic lattice in real space with a unit cell of 2a p  2a p  2a p . It is noteworthy that this pseudo fcc structure has also been reported in as-grown LCMO films on LaAlO 3 substrates [19].…”
Section: Electron Diffraction Patternssupporting
confidence: 71%
“…The aforementioned analysis of x-ray data showed that the out-of-plane lattice parameter c is larger for LSM/LAO. It is well known that LSM thin films grown on LAO substrates exhibit an out-of-plane uniaxial tensile strain and, correspondingly, an in-plane biaxial compression [9,10]. Assuming that the film is strained from the ideal bulk structure and that the structure is a single perovskite, the in-plane lattice parameter of film can be estimated from the unit cell volume in the bulk.…”
mentioning
confidence: 99%
“…The LCM2 film shows weak Bragg peaks on a background of the same smooth plateau. The out-of-plane lattice parameter for the LCM2 film, c ; 0.3866 nm, is very close to that for the bulk [13,14]. This suggests that the incipient crystalline phase grows in equilibrium conditions without a significant influence of the substrate and is formed through the amorphous state.…”
Section: Microstructure Of the Filmsmentioning
confidence: 56%
“…However, together with the perpendicular crystal axes, a tetragonal distortion of the lattice (c a ; 1.026) is also found in inset B. The estimated in-plane lattice parameter for the LCM3 film, a ; 0.3826 nm, is smaller than that for the bulk compound, a ; 0.3858 nm [14]. This difference leads to for- ; -0.83 and e ; 1.79%.…”
Section: Microstructure Of the Filmsmentioning
confidence: 90%
See 1 more Smart Citation